Trend of relations between morphological characteristics and motor abilities in preschool children - Bala, Gustav (Array, 2009)
Abstract: Measurements of eight anthropometric characteristics and a battery of seven motor tests were applied in a large sample of 1170 children, 565 boys and 605 girls aged 4 to 7.5 decimal years from preschool institutions in three towns in Vojvodina (Novi Sad, Sombor, and Ba~ka Palanka). Children were selected according to 0.5 decimal years in the mentioned age range. The status of boys and girls according to seven age categories, age-related differences between boys and girls, as well as the relations between anthropometric characteristics and motor abilities were analyzed by use of intercorrelation matrices and canonical correlation analysis. Generally, significant sex differences were found in anthropometric characteristics, i.e. the values of bone growth in length were higher in boys, while the values of voluminosity and subcutaneous adipose tissue were higher in girls.